Postoperative Breath-Holding Spells Requiring Cardiopulmonary Resuscitation After Cardiopulmonary Bypass - Rebecca Kreis PA-C; Jeffrey A. Robinson MD; Ali Ibrahimiye MD; Laura Ortmann MD (SAGE Publishing, 2022)
Breath-holding spells are common in childhood and can be associated with bradycardia and pulselessness. This report details severe breath-holding spells complicating postoperative management after atrial septal defect closure. The patient required cardiopulmonary resuscitation despite the use of a temporary pacemaker to prevent bradycardia. After multiple episodes of chest compressions, the decision was made to not intervene immediately to pulselessness and the patient was able to recover without further intervention.